2013
DOI: 10.1111/jep.12078
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and quality of clinical pathways in Swedish intensive care units: a national survey

Abstract: SUMMARY AimsTo identify the prevalence of Clinical Pathways (CPs) in Swedish Intensive Care Units (ICUs) and to explore the quality, content and evidence base of the documents in use.Methods A descriptive and explorative survey of all Swedish ICUs (N84) and a review of submitted examples of CPs (n12) were conducted.Results CPs were in use at 20% of the Swedish ICUs. There was a significant geographic variation but no relationships between the use of CPs and category of hospital, type of ICU, size of ICU or typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Local project groups should include persons who are able to appraise scientific literature [1]. The quality of CPs within ICUs [23], as well as in other settings in Sweden [35], varies and there are significant differences between the ICUs in the southern and northern regions regarding the use of CPs [23]. The present findings indicate a lack of national guidance and insufficient CP support at the local hospitals regarding the implementation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Local project groups should include persons who are able to appraise scientific literature [1]. The quality of CPs within ICUs [23], as well as in other settings in Sweden [35], varies and there are significant differences between the ICUs in the southern and northern regions regarding the use of CPs [23]. The present findings indicate a lack of national guidance and insufficient CP support at the local hospitals regarding the implementation.…”
Section: Discussionmentioning
confidence: 81%
“…A recent national survey reveals that many ICUs have plans for implementing CPs but CPs are actually in use at only 20% of the ICUs. Furthermore, the survey reveals that the quality of the CPs in use vary, with great differences regarding the content and extension as well as the degree to which the CPs are interprofessional, evidence‐based and renewed, which leads to concerns regarding the implementation process [23].…”
Section: Introductionmentioning
confidence: 99%
“…The use of pathways in ICUs seems promising, as it can contribute to increased adherence to best-practice guidelines, streamlined care, a decreased mechanical ventilation time, and reduced complications [ 10 14 ]. As pathways are still rarely utilized in ICUs, further implementation has the potential to benefit both patients and healthcare providers [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relative terms, developed countries have more extensive implementation of clinical pathways (17). As an example, a Swedish study indicated that clinical pathways were in use at 20% of Swedish intensive care units (ICUs) and a total of 56 clinical pathways were reported within a range of fi elds and areas (18). A study of clinical pathways in 17 member states of the European Union found that that the United Kingdom had the highest estimated level of pathway use, with a level reaching almost 45% in 2004.…”
Section: Standardized Clinical Pathways In Chinamentioning
confidence: 99%